GAMBARAN PENGETAHUAN DAN SIKAP IBU TENTANG PELAKSANAAN TOILET TRAINING PADA ANAK USIA 1-3 TAHUN DI WILAYAH KERJA POSYANDU DESA KUBANG JAYA KABUPATEN KAMPAR - Syari, Elfita; Chandra, Fifia; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTToilet training is a technique for teaching children to defecate and urinate in the toilet. Mother’s knowledge and attitude plays an important role in the implementation of toilet training. This study was conducted to know the mother’s knowledge and attitude about the implementation of toilet training toward the children ages 1-3 years old in the area of Posyandu Kubang Jaya village Kampar District. This study was conducted in the area of Posyandu Kubang Jaya village Kampar District. The design research of this study is a descriptive cross-sectional approach. The sample of this study were the mothers of 1-3 years old children. The minimum number of samples required were 79 mothers. The data was taken from interviews and questionnaires. Based on the result of this study, it shows that the most knowledge, attitude and the implementation of toilet training is in the sufficient category (76%), neutral (60.8%) and most of mothers (79.8%) have conducted toilet training. Age <18 months is the most age where the toilet training is implemented (61.9%). The most mothers who have do the toilet training are the mothers in the age of 20-35 years old (68.4%), high school educated mothers (45.6%), housewife (69.6%) and mothers with children(≤2 child) 45.6%. Female babies (45.6%) are the most numerous who have conducted toilet training. Mothers who have conducted toilet training mostly have sufficient knowledge (60.8%) and neutral (49.4%).Keywords: knowledge, attitude, implementation, toilet training, toddler child